2018 proceedings of the Eighth SIAM Workshop on Combinatorial Scientific Computing (CSC) - Manne, Fredrik; Sanders, Peter 1967-; Toledo, Sivan (Society for Industrial and Applied Mathematics, SIAM, 2018)
The papers in this volume were presented at CSC18, the 8th SIAM Workshop on Combinatorial Scientific Computing, held June 6-8, 2018 in Bergen, Norway. The CSC workshop series provides a forum for researchers from academia and industry interested in the interaction of combinatorial (discrete) mathematics and algorithms with computational science and engineering. CSC18 follows seven successful CSC workshops held roughly biennially, in February 2004, June 2005, February 2007, October 2009, May 2011, July 2014, and October 2016
Keywords: Computer programming; Congresses; Combinatorial analysis; Congresses; Science; Data processing; Congresses; Discrete mathematics and graph theory; Konferenzschrift